2016
DOI: 10.1080/09513590.2016.1257602
|View full text |Cite
|
Sign up to set email alerts
|

Standard hormone therapy is inadequate for bone density in premature ovarian insufficiency

Abstract: To assess standard dose hormone therapy (HT) and bone mass in premature ovarian insufficiency (POI), 239 women with POI, 132 using standard estrogen dose HT and 107 women without HT, were evaluated. All underwent bone mineral density (BMD) evaluation in the lumbar spine (LS) and total femur (TF). Mean age, age at last period and body mass index (BMI) for the untreated and for the HT groups were 38.1 ± 6.1 and 36.8 ± 7.3 years; 31.4 ± 7.3 and 30.7 ± 7.2 years; 26.6 ± 7.1 and 25.8 ± 4.6 kg/m, respectively, (p=NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Among the articles excluded through full text reading there were 12 excluded because the study participants were older than 40 years at the onset of treatment and 9 because the study interventions or outcomes were not compatible with the review entry criteria (Figure 1). We also excluded 5 studies that evaluated HT in women with POI but had a cross-sectional design (Kurabayashi et al, 1993;Madalinska et al, 2006;Bachelot et al, 2016;Giraldo et al, 2017;Benetti-Pinto et al, 2019).…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Among the articles excluded through full text reading there were 12 excluded because the study participants were older than 40 years at the onset of treatment and 9 because the study interventions or outcomes were not compatible with the review entry criteria (Figure 1). We also excluded 5 studies that evaluated HT in women with POI but had a cross-sectional design (Kurabayashi et al, 1993;Madalinska et al, 2006;Bachelot et al, 2016;Giraldo et al, 2017;Benetti-Pinto et al, 2019).…”
Section: Excluded Studiesmentioning
confidence: 99%
“…In general, these doses lead to clinical improvement and serum estradiol levels between 30-50 pg/mL, which correspond to the levels observed in the early follicular phase (68,80). A Brazilian study evaluating bone mass in patients with premature ovarian failure has shown that the doses of estrogen normally used in postmenopause were not adequate to reduce impaired spinal and femoral bone mass in younger women (81), although no consensus in the literature has established the required estrogen dose in this age group.…”
Section: Sex Steroid Replacement Therapymentioning
confidence: 99%
“…However, the other study showed estrogen therapy was not associated with a reduction in overall fracture risk (hazard ratio [HR], 0.90; 95% CI, 0.64-1.28) and osteoporotic fractures (HR, 0.80; 95% CI, 0.52-1.23) [29]. Another study also showed the standard dose of HT was not adequate for bone mineral density in premature ovarian failure women [32]. In this study, we found the association between estrogen therapy and the risk of osteoporosis and bone fracture.…”
Section: Comparison Group Without Oophorectomymentioning
confidence: 99%